Cellular Sources of Tenascin-C in Canine Mammary Carcinomas. (January 2015) - Yoshimura, H.; Michishita, M.; Ohkusu-Tsukada, K.; Matsuda, Y.; Ishiwata, T.; Naito, Z.; Takahashi, K.
Tenascin-C (Tn-C) is an extracellular matrix glycoprotein implicated in the progression of several human cancers. In canine mammary carcinomas, accumulation of Tn-C has been recognized in 3 different areas: regions of proliferating myoepithelial cells in complex carcinoma, basement membrane zone in low-grade simple carcinoma, and reactive stroma in high-grade simple carcinoma. To identify the Tn-C synthesizing cells in these areas, we utilized double-labeling immunohistochemistry, branched DNA in situ hybridization, and in situ hybridization–immunohistochemistry double-labeling techniques. In complex carcinomas, Tn-C was generated by proliferating myoepithelial cells. Tn-C in low-grade simple carcinomas was also derived from myoepithelial cells existing as a basal monolayer. However, stromal Tn-C in high-grade carcinomas was mainly synthesized by fibroblasts/myofibroblasts, similar to human breast cancer. Thus, the origin of Tn-C in canine mammary carcinomas differs between low- and high-grade malignancies. The role of myoepithelial cell-generated Tn-C is not yet understood.